Frontal lobe meningioma presenting with schizophrenia-like symptoms: An organic cause of psychotic disorder - Chawisa Suradom (2020)
© BMJ Publishing Group Limited 2020. No commercial re-use. See rights and permissions. Published by BMJ. A 51-year-old woman had been diagnosed and treated for schizophrenia for 10 years. Two weeks prior to admission, she developed headache and diplopia. Then, she was found unconscious and was sent to the hospital. A tumour in the left frontal lobe of the brain, causing brain herniation, was diagnosed and surgical excision of tumour was performed immediately. The psychotic symptoms of the patient were completely resolved after surgery. The histological diagnosis was meningioma. This case demonstrates an uncommon presentation of meningioma, the most common primary brain tumour. Patients presenting with psychotic symptoms may be misdiagnosed with schizophrenia, when a tumour is present, allowing the tumour to grow and causing associated complications. Early diagnosis and treatment could prevent mortality and morbidity. The treating physician should be aware of organic possibilities and carefully search for atypical presentations of psychiatric disorders in their patients.